Pengembangan multimedia pembelajaran interaktif articulate storyline terintegrasi microgames pada materi proses digesti manusia kelas XI - Malvin Prima Soyoga; Meti Indrowati; Umi Fatmawati (Universitas Sebelas Maret, 2025)
ENThis study aims to (1) develop interactive learning multimedia Articulate Storyline integrated with microgames on the material of human digestion process in class XI, (2) test the feasibility of interactive learning multimedia Articulate Storyline integrated with microgames on the material of human digestion process in class XI. This type of research is Research and Development (R&D) with the ADDIE model, which is modified only to the Develop stage and combined with a mixed method sequential exploratory design approach. The research data collection technique was carried out using a questionnaire. The data analysis technique was carried out using descriptive data analysis. The research results showed that the product developed has interactive, independent, and convergent properties and is unique, namely, the insertion of 12 types of microgames in the content of the digestion process material. The feasibility value of the product developed showed 87% responses from media experts, 87% from learning experts, 91.3% from teacher responses (practitioners), and 90.3% from student responses. Thus, interactive learning multimedia based on Articulate Storyline integrated with microgames on the material of the digestion process is declared very feasible to be used as a learning media for biology in class XI.IDPenelitian ini bertujuan untuk: (1) mengembangkan multimedia pembelajaran interaktif Articulate Storyline terintegrasi microgames pada materi proses digesti manusia di kelas XI, (2) menguji kelayakan multimedia pembelajaran interaktif Articulate Storyline terintegrasi microgames pada materi proses digesti manusia di kelas XI. Jenis penelitian ini adalah Research and Development (R&D) dengan model ADDIE, yang dimodifikasi hanya sampai tahapan Develop dan dipadukan dengan pendekatan mixed method sequential exploratory design. Teknik pengumpulan data penelitian dilakukan dengan kuesioner. Teknik analisis data dilakukan dengan analisis data secara deskriptif. Hasil penelitian yang dilakukan menunjukkan produk yang dikembangkan memiliki sifat interaktif, mandiri, dan konvergen, serta memiliki keunikan yakni terdapat penyisipan 12 macam microgames pada konten materi proses digesti. Nilai kelayakan produk yang dikembangkan menunjukkan sebesar 87% respon dari ahli media, 87% dari ahli pembelajaran, 91,3% dari respon guru (praktisi), dan 90,3% dari respon siswa. Dengan demikian, multimedia pembelajaran interaktif berbasis Articulate Storyline terintegrasi microgames materi proses digesti dinyatakan sangat layak untuk digunakan sebagai media pembelajaran biologi kelas XI.